2014
DOI: 10.1016/j.cmet.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Dependent Metabolic Reprogramming Regulates Tumor Cell Histone Acetylation

Abstract: SUMMARY Histone acetylation plays important roles in gene regulation, DNA replication, and the response to DNA damage, and it is frequently deregulated in tumors. We postulated that tumor cell histone acetylation levels are determined in part by changes in acetyl-CoA availability mediated by oncogenic metabolic reprogramming. Here, we demonstrate that acetyl-CoA is dynamically regulated by glucose availability in cancer cells and that the ratio of acetyl-CoA: coenzyme A within the nucleus modulates global hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
501
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(530 citation statements)
references
References 55 publications
27
501
2
Order By: Relevance
“…Possibly, other thiol-containing molecules, such as GSH could serve as the acetyl group acceptor, considering that the cellular CoA is around 10 µM while GSH is 1 to 7 mM (Fig. 3b), and similar concentration values in different types of cells or tissues were also reported by others [28][29][30] . Low levels of CoA and high levels of GSH were also observed in autochthonous mouse tumors providing a physiological context for this occurrence (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Possibly, other thiol-containing molecules, such as GSH could serve as the acetyl group acceptor, considering that the cellular CoA is around 10 µM while GSH is 1 to 7 mM (Fig. 3b), and similar concentration values in different types of cells or tissues were also reported by others [28][29][30] . Low levels of CoA and high levels of GSH were also observed in autochthonous mouse tumors providing a physiological context for this occurrence (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Combined with the observation that free CoA is present at roughly equimolar concentrations to acetyl-CoA in cells (Gao et al, 2007;Lee et al, 2014), it is plausible that the ratio of acetyl-CoA to CoA may modulate KAT activity (Albaugh et al, 2011). Interestingly, a recent study profiling the acyl chain specificity of Gcn5 observed potent inhibition by long fatty acyl-CoA molecules like palmitoyl-CoA (Montgomery et al), further supporting the idea that acyl-CoA molecules may function as natural KAT inhibitors.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, intracellular concentrations of different acyl-CoA species change in response to metabolic fluctuations (Hosokawa et al, 1986;Palladino et al, 2012;King & Reiss, 1985). For example, measurements of the intracellular concentration of acetyl-CoA vary based on nutrient availability, and range from 3 to 30 µM in yeast (Cai et al, 2011;Weinert, 2014) and 2 to 13 µM in human cells (Lee et al, 2014). With a K m for acetyl-CoA of 0.91 ± 0.09 µM (Figure 5A), acetyl-CoA availability may regulate the activity of human Gcn5 (Albaugh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The starvation-induced reduction in IGF1 bioavailability would reduce the AKT1 (AKT serine/threonine kinase 1)-dependent activity of the acetyl-CoA-generating enzyme ACLY (ATP citrate lyase). 49 If a reduced flux in acetyl-CoA production was linked to immediate deacetylation, then the acetate generated as a result of histone deacetylation would cause an immediate increase in free acetate, which in turn would constitute a source for acetyl-CoA, hence maintaining stable acetyl-CoA levels. 50,51 Nonetheless, this hypothetical conjecture requires further exploration.…”
Section: Discussionmentioning
confidence: 99%